A Review of Customary Law and Islamic Law on Marriage of Couples Motivated by Behavior Violating Norms - Prayetno, Dwi (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This study aims to examine the practice of marriage motivated by behavior that violates norms, both from the perspective of customary law and Islamic law. This phenomenon is often found in various communities, especially when couples who commit social offenses, such as extramarital relationships, are then